LANK LEEF DIE DOOIES: OOR POSTMORTEM FOTOGRAFIE, DODEMASKERS, GELOOFSGETUIES, VOORVADERS EN DOMINEE-PORTRETTE - Wepener, Cas (Scriptura, 2003)
By making use of qualitative interference as methodological starting point, this article sets out to compare some "qualities" inherent in five distinct phenomena. The phenomena under scrutiny are postmortem photography, death masks, saints, ancestors and portraits of ministers. Each one of these phenomena is firstly (briefly) opened as a source in order to shed light on some of it’s important aspects. Secondly some qualities that were derived from these sources are compared for qualitative interference. This is done to show that the essence of photography as a medium makes it an excellent source for the inculturation of the honoring of the ancestors (the so-called living dead) in the liturgy of African churches.